ضوابط الإرهاب في الإسلام ومُحاربتهِ للعُنف (Terrorism restrictions in Islam and fighting violence) - Mohamed Fathy, Mohamed Abdelgelil; Husin Ali Abdullah, Al-Thalaaya (2020)
There has been a hideous misunderstanding and a mismatch between the Islamic concept and the Western concept of terrorism. This was not the direct result of the intercivilizational conflict and the scientific and intellectual vacuum in the contemporary Islamic nation, but there are some forces hostile to Islam, its culture, its civilization, the glories of its nation and its bright history of cultural contribution and creative cultural achievement. The description of Islam as the religion of terrorism and extremism is inaccurate. The current research addresses this point. The aim of the research is to clarify the issue of terrorism in Islam, and that it has controls and conditions to be observed; otherwise, any action is deemed as violent and rejected by Islam which condemns and punishes the doer who solely bears the accountability of his own actions. The researcher reached several conclusions, including but not limited to: To strike fear in the hearts of the enemy without shedding blood is the Islamic concept derived from the word irhaab. However, to resort to violence, to spread crimes, and to cause chaos and corruption at the individual or collective level is not accepted by Islam.